Social Status Shift and Collapse of Uleebalang in Aceh of 1900-1946 - Muhammad Muhammad; Sukiman Sukiman; Irwansyah Irwansyah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This paper explores the Social Status Shift and Collapse of Uleebalang in Aceh of 1900-1946. The conflict between ulama and ulebalang increasingly entered a critical phase, especially after news of Japan's defeat. This research is conducted by using qualitative research design. The results shows that the surrender of the uleebalang did not dampen the ulama's determination to continue to expel the Dutch from the land of Aceh in various regions, both in Aceh City, Pidie, North Aceh, West Aceh, Central Aceh and Southeast Aceh fall on the battlefield. The Aceh War had a great impact on the people of Aceh, especially the scholars. The direct impact of the Aceh war can be seen from the division of ulama into three groups, there are 1) The ulama who was the Kadli in the government of the uleebalang who recognized Dutch sovereignty; 2) The ulama who only give religious lessons in dayah-dayah; and 3) The ulama who still continued the struggle against the Dutch. In addition, the fundamental impact is the strengthening of the position of ulama in Acehnese society. Another impact is the widening of the distance between the ulama and the uleebalang. The Dutch tried to break the Acehnese community through politics.